KPol 2021
DOI: 10.51738/kpolisa2021.18.1p.1.04
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Education and Information as a Cause of Trafficking of Women for Sexual Exploitation

Abstract: Trafficking of women for sexual exploitation, as one of the most common forms of human trafficking, affects all countries regardless of the level of development, and all social groups, regardless of financial security, level of education, and other important parameters. Having in mind the core problems that victims of human trafficking (especially women) face, this paper, in addition to a general review of the causes of human trafficking and general observations on trafficking in women and elements of sexual e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Studies in other countries found that education, or the lack thereof, plays a pivotal role as a preventive tool and a point of vulnerability. When families cannot afford education or when children are compelled to leave school to work, they become more susceptible to exploitation (Matijašević & Dragojlović, 2021). Human trafficking represents another dimension of cross-border organized crime driven by poverty in the country.…”
Section: Desperation Fuels Vulnerabilitymentioning
confidence: 99%
“…Studies in other countries found that education, or the lack thereof, plays a pivotal role as a preventive tool and a point of vulnerability. When families cannot afford education or when children are compelled to leave school to work, they become more susceptible to exploitation (Matijašević & Dragojlović, 2021). Human trafficking represents another dimension of cross-border organized crime driven by poverty in the country.…”
Section: Desperation Fuels Vulnerabilitymentioning
confidence: 99%